Reassessing order and disorder in the Middle East : regional imbalance or disintegration? - Mason, Robert, 1979- (Rowman & Littlefield, 2017)
Case studies help identify the emerging trends and influences that dominate the political decision making and policy behavior of many states in the Middle East. The chapters investigate foreign policy challenges and debates in various states, changing relations and balance of power between them, and the continuing role of the US in the region.